Exploring the interplay of parenting styles, basic empathy, domestic violence, and bystander behavior in adolescent school bullying: a moderated mediation analysis - Zhong, Lujie; Ying, Yutong; Zeng, Chunni; Li, Jiaying; Li, Yun (Frontiers in Psychiatry, 2024)
Introduction: This study investigates how parental styles, basic empathy, and family violence influence adolescents' bystander behaviors in school bullying. Methods: A survey was conducted with 1,067 students from three middle schools in southern China. Multifactor logistic regression and a moderated mediation model were employed to analyze the relationships between positive and negative parental styles, basic empathy, and bystander behaviors. Results: The study found significant correlations and predictive relationships: Positive parental styles were strongly associated with increased basic empathy (r = 0.29, p < 0.01) and behaviors that protect victims (r = 0.29, p < 0.01). In contrast, negative parental styles correlated positively with behaviors that support bullying (r = 0.12, p < 0.01) and instances of family violence (r = 0.62, p < 0.01). Basic empathy negatively predicted behaviors that promote bullying (β = -0.098, p < 0.01) and positively predicted protective behaviors toward victims (β = 0.249, p < 0.001). Furthermore, family violence weakened the positive effects of positive parental styles on both empathy (β = -0.075, p < 0.001) and protective behaviors (β = -0.025, p < 0.01). Conclusion: The findings indicate that positive parental styles indirectly promote adolescents' victim protector behaviors by enhancing their basic empathy, underscoring the importance of emotional cultivation. Meanwhile, family violence weakens the positive impact of these parental styles on basic empathy and protective behaviors, harming adolescents' emotional security and behavioral norms.